The Impact of Corporate Social Responsibility on Business Performances through Green Supply Chain Management - Avila Garcia Ruben Estuardo (Graduate School of International Studies Ajou University, 2014)
Previous research has suggested that a fair strategy of corporate social responsibility (CSR) positively influences business performances; however, less attention has been paid to the effect that CSR could have on business performances through environmental efforts. As the public is becoming more aware of the environmental issues and the consequences of global warming, the consumers all over the world are already questioning the companies about the products they are selling. The purpose of this research is to bring some evidence from Guatemalan firms to examine the relationship between CSR, GSCM practices, and business performances. After reviewing the extensive literature, a research model was developed including five constructs: CSR, GSCM practices, environmental, economic and operational performances. The statistical analyses were based on the primary data collected from a survey questionnaire, responded by 93 different company managers in the Republic of Guatemala. Furthermore, structural equation modeling was utilized to analyze the data and to test the hypotheses. The results of the analyses showed that there is a significant influence of CSR on the adoption of GSCM practices. It was also found that implementation of GSCM practices has a significant influence on environmental, economic and operational performances. The relationships among the business performances was also studied, in this sense, it was found that environmental performance has a significant impact on economic and operational performance. Finally, the mediating effect of GSCM practices on the relationships between CSR and business performances was also investigated, and it was found that GSCM has a mediating role on the relationship between CSR and environmental and economic performance, but not with operational performance. Keywords: corporate social responsibility, CSR in Guatemala, green supply chain management, environmental performance, economic performance, operational performance, structural equation modeling.
학위논문(석사)--아주대학교 Graduate School of International Studies :국제경영학과,2014. 8